2021
DOI: 10.26434/chemrxiv.14317205
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Inverse Thermogelling Bioink Based on an ABA Type Poly(2-Oxazoline) Amphiphile

Abstract: Hydrogels are key components in several biomedical research areas such as biofabrication. Here, a novel ABA-type triblock copolymer is introduced that undergoes a inverse thermogelation, i.e. it forms a hydrogel about cooling aqueous polymer solutions. The macroporous hydrogel was rheologically investigate in detail and used for 3D printing using an extrusion based printer. Preliminary experiment show very good cytocompatibility of NIH 3T3 cells also after printing and the possibility to combine the novel mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…More recently, Lübtow et al reported on the development of ABA triblock copolymer comprised of pMeOx (A) and poly(2-iso-butyl-2-oxazoline) (p i BuOx) (B) which form thermogels at 20 wt.% but its rheological characteristics, in particular its low yield stress were not conducive for extrusion-based 3D printing [ 48 ]. In addition, Hahn et al reported on several ABA POx/POzi-based triblock copolymers exhibiting inverse gelation [ 6 , 61 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Lübtow et al reported on the development of ABA triblock copolymer comprised of pMeOx (A) and poly(2-iso-butyl-2-oxazoline) (p i BuOx) (B) which form thermogels at 20 wt.% but its rheological characteristics, in particular its low yield stress were not conducive for extrusion-based 3D printing [ 48 ]. In addition, Hahn et al reported on several ABA POx/POzi-based triblock copolymers exhibiting inverse gelation [ 6 , 61 ].…”
Section: Introductionmentioning
confidence: 99%